2020
DOI: 10.3390/su12093509
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Heritage Systems and Landscape Perception among Tourists. The Case of Lamole, Chianti (Italy)

Abstract: The Globally Important Agricultural Heritage Systems (GIAHS) program, promoted by the Food and Agriculture Organization (FAO), recognizes the multifunctional role of agricultural heritage systems. Traditional terraced landscapes represent important touristic destinations, and Chianti is one of the most well-known areas of Italy for rural tourism. The high-quality landscape of Lamole, consisting of forests and terraced agricultural areas, is included in the Italian National Register of Historical Rural Landscap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 50 publications
1
28
0
1
Order By: Relevance
“…National policies are targeted on preserving such agricultural heritage sites around the world, but also promote them as touristic attractions, which maintain their traditional and historical character [73,74]. A survey on terraced landscape perception in the Chianti region (Italy) showed that tourists clearly prefer visiting a traditional landscape, which is comprised of a mosaic of agricultural patches with dry-stone terraces and forests [75]. In Greece the majority of island terraces are neglected and only part-time farmers acknowledge the productive, ecological, aesthetic and historical value of terraces, although terrace farming still remains hard-work.…”
Section: Discussionmentioning
confidence: 99%
“…National policies are targeted on preserving such agricultural heritage sites around the world, but also promote them as touristic attractions, which maintain their traditional and historical character [73,74]. A survey on terraced landscape perception in the Chianti region (Italy) showed that tourists clearly prefer visiting a traditional landscape, which is comprised of a mosaic of agricultural patches with dry-stone terraces and forests [75]. In Greece the majority of island terraces are neglected and only part-time farmers acknowledge the productive, ecological, aesthetic and historical value of terraces, although terrace farming still remains hard-work.…”
Section: Discussionmentioning
confidence: 99%
“…This is beneficial as an investment in the mid to long term for the local communities, also because it takes into account the sustainable development goals as defined by the United Nations. Analogously to the Qingtian Rice-Fish Co-culture system, the successful GIAHS cases in the world have had similar situations by raising prices of distinctive agricultural products to drive local economic development, rural community construction, and cultural inheritance, such as Sado's Satoyama in Harmony with Japanese Crested Ibis in Japan [16], the agriculture system in Chiloé Island of Chile [17,18], the agroforestry heritage systems in the mountain oases of Tunisia [19], and the traditional terraced landscapes in Chianti of Italy [20].…”
Section: Introductionmentioning
confidence: 99%
“…People care about the changing landscape. A survey in Lamole, Chianti (Italy) demonstrated that tourists strongly preferred a traditional landscape consisting of a mosaic of fields with dry-stone terraces and forests, and that the landscape diversification was similar to that from 180 years ago [59]. For Tuscany (Italy), the landscape is the fundamental value from the cultural, economic, environmental, and social perspective [60].…”
Section: Discussionmentioning
confidence: 99%